Case report: Surgical treatment and long-term successful outcome of a spinal intramedullary vascular malformation in a dog - Santifort, Koen M.; Plonek, Marta; Grinwis, Guy C. M.; Carrera, Ines; Platt, Simon (Frontiers in Veterinary Science, 2023)
A 3.5-year-old male intact Staffordshire terrier crossbreed dog was presented with a one-week history of progressive paraparesis with fecal and urinary incontinence. Neurological examination was consistent with a T3-L3 myelopathy. A magnetic resonance imaging study revealed the presence of a well-circumscribed hemorrhagic space-occupying lesion at the level of T12, suspected to be a vascular malformation, such as cavernoma or arteriovenous fistula, primary hematoma or hamartoma; less likely considerations included hemorrhagic inflammation or hemorrhagic primary or secondary neoplasia. A dorsal laminectomy, durotomy, and midline dorsal myelotomy were performed with a surgical microscope, and the vascular lesion was identified and removed. Histological examination of surgical samples yielded fibrin, hemorrhage, hematoidin pigment, and some neural tissue. Although a lining wall was visualized during surgery consistent with a vascular malformation, there was no histological confirmation of such a structure, hampering definitive classification of the lesion. There was no gross or histopathological evidence that would support a diagnosis of a hamartoma or benign neoplasia. The dog was paraplegic with intact nociception the day following surgery. Ambulation was recovered within 2 weeks. Progressive and complete recovery of neurological function was seen over the next 12 weeks. No recurrence of neurological dysfunction was seen over a 12-month follow-up period. Surgical treatment should be considered in dogs with spinal intramedullary vascular lesions which can have a successful long-term outcome.